An Observational Study of Therapeutic Hypothermia and Factors Associated With Mortality in Late-Preterm and Term Neonates With Hypoxic-Ischemic Encephalopathy in a Middle-Income Country - Boo, Nem Yun; Neoh, Siew Hong; Chee, Seok Chiong, for the Malaysian National Neonatal Registry (Frontiers in Pediatrics, 2022)
Objectives: To investigate the types of therapeutic hypothermia (TH) used and risk factors associated with mortality in late-preterm and term neonates (LPTN, gestation ≥35 weeks) with hypoxic-ischaemic encephalopathy (HIE) in a middle-income country. Design: Observational retrospective cohort study. Setting: 44 NICUs in the Malaysian National Neonatal Registry. Patients: All LPTN without major malformations and diagnosed to have HIE. Main outcome measures: In-hospital mortality, types of TH (no TH, TH using commercially available servo-controlled devices (SCDs), passive TH by exposing neonates to NICU’s air-conditioned ambient temperature with/without use of cooled gel packs (P±CGPs)). Results: Of a total of 2761 HIE neonates, 66.3% received TH. All NICUs provided TH; 55.4% NICUs had SCDs which was administered to 43.6% (248/569) of severe, 51.6% (636/1232) of moderate, and 18.6% (179/960) of mild HIE neonates. P±CGPs was used on 26.9% of severe, 33.4% of moderate, and 21.1% of mild HIE neonates. There were 338 deaths. Multiple logistic regression analysis showed that 5-minute Apgar scores <5 (aOR: 1.436; 95%CI: 1.019, 2.023), Caesarean section (aOR: 2.335; 95%CI: 1.700, 3.207), receiving no TH (aOR: 4.749; 95%CI: 3.201, 7.045), TH using P±CPGs (aOR: 1.553; 95%CI: 1.031, 2.338), NICUs admitted <50 HIE cases (aOR: 1.898; 95%CI: 1.225, 2.940), NICUs admitted 50-<100 HIE cases (aOR: 1.552; 95%CI: 1.065, 2.260), moderate HIE (aOR: 2.823; 95%CI: 1.495, 5.333), severe HIE (aOR: 34.925, 95%CI: 18..478, 66.012), Thompson scores 7-13 (aOR: 1.776; 95%CI: 1.023,3.082), Thompson scores ≥14 (aOR: 3.641; 95%CI: 2.000, 6.629), pneumothorax (aOR: 3.435; 95%CI: 1.996, 5.914), and foreigners (aOR: 1.646; 95%CI: 1.006,2.692) were significant risk factors associated with mortality. Conclusion: Both SCD and P±CGP were used for TH. Moderate/severe HIE and receiving passive/no TH were among the risk factors associated with mortality.